2022
DOI: 10.1101/2022.04.26.22274257
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immediate, remote smoking cessation intervention in participants undergoing a targeted lung health check: QuLIT2 a randomised controlled trial

Abstract: BackgroundLung cancer screening programs provide an opportunity to support smokers to quit, but the most appropriate model for delivery remains to be determined. Immediate face to face smoking cessation support for people undergoing screening can increase quit rates, but it is not known whether remote delivery of immediate smoking cessation counselling and pharmacotherapy in this context is also effective.Materials and MethodsIn a single-blind randomised controlled trial, smokers aged 55-75 years attending a T… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(24 citation statements)
references
References 20 publications
(39 reference statements)
0
24
0
Order By: Relevance
“…A 2019 systematic review found moderate-certainty evidence that proactive telephone counselling helps smokers to quit smoking, but insufficient evidence to assess whether telephone counselling provided as an adjunct to other smoking cessation therapies has any additional effect [9]. There are promising signs that remote cessation services operated with some success in the pandemic; for example, studies required to change interventions from faceto-face behavioural support to remote behavioural support due to the pandemic found that quit rates [10] and clinic visits [11] for those in the intervention arm were similar for face-to-face and remote delivery. In Canada, it was found that the move to phone-based care for smoking cessation for cancer patients during the COVID-19 pandemic sometimes decreased counselling interruptions and improved follow-up rates [7].…”
Section: Global Smoking Cessation Services In Covid-19 Pandemicmentioning
confidence: 99%
“…A 2019 systematic review found moderate-certainty evidence that proactive telephone counselling helps smokers to quit smoking, but insufficient evidence to assess whether telephone counselling provided as an adjunct to other smoking cessation therapies has any additional effect [9]. There are promising signs that remote cessation services operated with some success in the pandemic; for example, studies required to change interventions from faceto-face behavioural support to remote behavioural support due to the pandemic found that quit rates [10] and clinic visits [11] for those in the intervention arm were similar for face-to-face and remote delivery. In Canada, it was found that the move to phone-based care for smoking cessation for cancer patients during the COVID-19 pandemic sometimes decreased counselling interruptions and improved follow-up rates [7].…”
Section: Global Smoking Cessation Services In Covid-19 Pandemicmentioning
confidence: 99%
“…Ten studies were RCT (3241) and 3 used an observational study with control group design (33, 42, 43) (Table 1). The studies were published between 2004 and 2022, involved a total of 5076 people who smoked, with sample sizes ranging from 18 to 1248.…”
Section: Resultsmentioning
confidence: 99%
“…Studies investigated effectiveness of smoking cessation interventions as follows: single, in clinic session of behavioural counselling (44), single, in clinic session of behavioural counselling and audio materials (36), single in clinic behavioural counselling, plus NRT and subsequent weekly telephone calls (34), internet self-help materials (33), tailored information leaflet (40), 2 behavioural support calls and Quitline (42), multiple weekly behavioural support calls (37, 39), multiple weekly behavioural support calls and pharmacotherapy, (38, 41), multiple weekly behavioural support, in clinic plus pharmacotherapy (32, 43) or e-cigarettes (35). Timing of the intervention delivery varied across included studies from immediately on the day of the screening clinic to 5 months after screening, average length of interventions was 13.2±13.6 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations